Evaluation of Stability and Effect of Gripping Method on a Laser-Induced Liquid Jet Hand Applicator for Usability Improvement. (September 2014) - Kato, Takashi; Arafune, Tatsuhiko; Washio, Toshikatsu; Yamauchi, Yasushi; Nakagawa, Atsuhiro; Ogawa, Yoshikazu; Tominaga, Teiji; Sakuma, Ichiro; Kobayashi, Etsuko
We developed a pulsed laser-induced liquid jet (LILJ) system to dissect tumor tissues while preserving fine blood vessels within deep and narrow working spaces and evaluated its utility and safety. However, the hand applicator of LILJ is heavy for the operator because of the torque generated by some of the accessories. Consequently, the operator cannot work with precision. To overcome this problem, we ergonomically redesigned the hand applicator of LILJ. Here, we report an assessment of the redesigned hand applicator's usability and stability that were evaluated by using the torque generated around the center of gravity of the hand applicator and the hit probability. We considered the load on the hand by force measured using a force-sensitive sensor attached to the hand applicator. We showed that three out of five subjects were able to generate enough force equally to stabilize the position of the proposed hand applicator after a disturbance was generated and were able to reduce the force enough to control the disturbance.